Gut microbiota: A new piece in understanding hepatocarcinogenesis. (1st April 2020) - Zhou, An; Tang, Li; Zeng, Shuo; Lei, Yuanyuan; Yang, Shiming; Tang, Bo
Abstract: The gut microbiota forms a symbiotic relationship with the host and benefits the body in many critical aspects of life. However, immune system defects, alterations in the gut microbiota and environmental changes can destroy this symbiotic relationship and may lead to diseases, including cancer. Due to the anatomic and functional connection of the gut and liver, increasing studies show the important role of the gut microbiota in the carcinogenesis of hepatocellular carcinoma (HCC). In this manuscript, we review the available evidence and analyze some potential mechanisms of the gut microbiota, including bacterial dysbiosis, lipopolysaccharide (LPS), and genotoxins, in the progression and promotion of HCC. Furthermore, we discuss the possible therapeutic applications of probiotics, chemotherapy modulation, immunotherapy, targeted drugs and fecal microbiota transplantation (FMT) in targeting the gut microbiota. Highlights: The gut microbiota plays an important role in carcinogenesis of hepatocellular carcinoma (HCC). Dysbiosis of gut microbiota promote the inflammation of liver and finally lead to the development of HCC. Targeting gut microbiota might be potential strategy for HCC treatment.